Reputational Risk in the Social Media Era: A Case Study of Crisis Management Strategies for Major Brands in Indonesia - Tri Warcono Adi; Susi Arijanti (Oikonomia : Journal of Management Economics and Accounting, 2025)
The development of digital technology has transformed the public communication landscape, with social media becoming the primary arena for interaction between companies and their audiences. The rapid flow of information on platforms like Instagram, Twitter, TikTok, and Facebook makes corporate reputations highly vulnerable to shifts in public perception that can occur within minutes. This study examines the crisis management strategies of major Indonesian brands in addressing reputational risk in the social media era. Using a qualitative, case study-based approach, data was collected through in-depth interviews, document analysis, and online observations. The analysis was conducted using the Miles & Huberman interactive model with triangulation of sources and methods. The results show that reputational risk is influenced by a combination of public expectations, user-generated narratives, and algorithmic logic, accelerating issue escalation. Defensive responses and delays in clarification have been shown to exacerbate crises, while swift, transparent, and empathetic strategies accelerate reputation recovery. Effective crisis management requires an integration of reactive and proactive approaches, supported by a continuous monitoring system, adaptive playbooks, and robust human resource capabilities. These findings emphasize that reputation management in the digital era must focus on building public trust through transparency, accountability, and continuous learning, enabling companies to survive and adapt to the ever-changing dynamics of the social media ecosystem